Immunohistochemical analysis of changes in signaling pathway activation downstream of growth factor receptors in pancreatic duct cell carcinogenesis - Pham, Nhu-An (BioMed Central, 2008)
BACKGROUND: The pathogenesis of pancreatic ductal adenocarcinoma (PDAC) involves multi-stage development of molecular aberrations affecting signaling pathways that regulate cancer growth and progression. This study was performed to gain a better understanding of the abnormal signaling that occurs in PDAC compared with normal duct epithelia. METHODS: We performed immunohistochemistry on a tissue microarray of 26 PDAC, 13 normal appearing adjacent pancreatic ductal epithelia, and 12 normal non-PDAC ducts. We compared the levels of 18 signaling proteins including growth factor receptors, tumor suppressors and 13 of their putative downstream phosphorylated (p-) signal transducers in PDAC to those in normal ductal epithelia. RESULTS: The overall profiles of signaling protein expression levels, activation states and sub-cellular distribution in PDAC cells were distinguishable from non-neoplastic ductal epithelia. The ERK pathway activation was correlated with high levels of (S2448)p-mTOR (100%, p = 0.05), (T389)p-S6K (100%, p = 0.02 and (S235/236)p-S6 (86%, p = 0.005). Additionally, (T389)p-S6K correlated with (S727)p-STAT3 (86%, p = 0.005). Advanced tumors with lymph node metastasis were characterized by high levels of (S276)p-NFκB (100%, p = 0.05) and (S9)p-GSK3β (100%, p = 0.05). High levels of PKBβ/AKT2, EGFR, as well as nuclear (T202/Y204)p-ERK and (T180/Y182)p-p38 were observed in normal ducts adjacent to PDAC compared with non-cancerous pancreas. CONCLUSION: Multiple signaling proteins are activated in pancreatic duct cell carcinogenesis including those associated with the ERK, PKB/AKT, mTOR and STAT3 pathways. The ERK pathway activation appears also increased in duct epithelia adjacent to carcinoma, suggesting tumor micro-environmental effects.